Governance, debt service, information technology and access to electricity in Africa - Simplice Asongu; Sara Le Roux (African Governance and Development Institute (AGDI), 2024)
The study investigates the role of governance (i.e., 'voice & accountability', political stability/no violence, regulatory quality, government effectiveness, corruption-control and the rule of law) in the incidence of short-term debt services on infrastructure development in the perspective of telecommunication infrastructure and access to electricity. The focus of the study is on 52 African countries for the period 2002-2021. The generalized method of moments is employed as estimation strategy and the following findings are established. Debt service has a negative unconditional effect on access to electricity and telecommunication infrastructure. Governance dynamics moderate the negative effect of debt service on infrastructure dynamics. Effective moderation is from regulatory quality and corruption-control for access to electricity and from government effectiveness, regulatory quality, corruption-control and rule of law, for telecommunication infrastructure. Policy implications are discussed.
Keywords: F34; H63; O10; O40; O55; 330; Debt service; governance; information technology; access to electricity; Africa